The Safety and Health Management at Highway Construction Site in Malaysia - RAMASAMY, KESSHALA; ALI TIGHNAVARD BALASBANEH (Recent Trends in Civil Engineering and Built Environment, 2023)
The construction industry is one of the most dangerous and high-risk work industry in the world. Therefore, safety and health management at highway construction is not applied systematically, accidents will arise, its will literally affect to Malaysia’s economic growth in future .Moreover, highway construction carry significant risks.The most common factors that contribute to these risks include inefficient planning, unexpected delays, poor quality equipment , and inadequate oversight.A questionnaire survey was conducted, targeting respondents who are highway projects under construction at Wilayah Persekutuan Kuala Lumpur.To determine respondent demographics, descriptive data were examined using a frequency and percent distribution. During this period, the mean score and Relative Importance Index were used to describe consensus on health and safety management in highway construction (RII). The findings of this study will assist practitioners in paying greater attention to health and safety management issues that will effect the success of security and health management for highway building projects.